The Effect of Dayak Onion Water (Eleutherin Palm folia) to Reduction of Blood Pressure on Hypertension Patients - Susanti, Veronika; Setiani, Diah; Shoufiah, Rahmawati (Rifa'Institute, 2023)
Introduction: Efforts to control hypertension by consuming antihypertensive drugs in the long term can cause Drug Related Problems, an unexpected condition experienced by the patient concerned, which may be caused by involving medication therapy given to the patient, which can actually or potentially affect the patient's condition. patient such as non-compliance, drug interactions, allergies to prescribed drugs, so it is necessary to look for treatments made from natural plants, one of which is Dayak onion. Objective: To determine the effect of dayak onion steeping water (Eleutherine palmifolia) on reducing blood pressure in hypertensive patients in the working area of the Gemuhan Asa Auxiliary Community Health Center. Methods: The type and research design used in this study was a quasi-experimental or quasi-experimental because the experiment was carried out in the community. Result and Discussion: p-value 0.000 (< 0.05) means that there is an effect of giving Dayak Onion (Eleutherine Palmifolia) Brewed Water on Blood Pressure Reduction in Hypertension Patients in the Working Area of ??Pembantu Gemuhan Asa Health Center. Conclusion: There is an effect of giving Dayak Onion (Eleutherine Palmifolia) Brewed Water on Blood Pressure Reduction in Hypertension Patients in the Working Area of ??Pembantu Gemuhan Asa Health Center.